Pengaruh Lingkungan Kerja, Gaya Kepemimpinan Islami dan Kompensasi Terhadap Loyalitas Kerja Karyawan: Work Environment, Islamic Leadership Style, Compensation, Employee Loyalty - Ahmad Setiyono; Hanifah Mulyadi; Hasni, Gina Atikah (Benefit: Jurnal Manajemen dan Bisnis, 2024)
Employees are the most important element in the organization that serves as a tool to improve company performance. company performance will continue to increase if there is a sense of loyalty among employees to the company. there are many factors that can affect employee loyalty, some of the factors that will be discussed include work environment factors, Islamic leadership styles and compensation. This study aims to determine whether there is an effect of work environment variables, Islamic leadership style and compensation on employee loyalty at CV. Pearl of the Earth Gemolong, Sragen, Central Java. The sample in this study amounted to 35 employees at CV. Pearl of the Earth Gemolong, Sragen, Central Java. The method in this study uses quantitative methods with data collection techniques using questionnaire data with the help of the IBM SPSS 20 software test tool for windows. The results showed that the work environment and compensation had no effect on employee loyalty, while the Islamic leadership style had a significant effect on employee loyalty. The three variables of work environment, Islamic leadership style and compensation simultaneously affect on employee loyalty.